2010
DOI: 10.1016/j.biopsych.2009.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Generalization in Schizophrenia: Effects of Disease and Antipsychotic Drug Treatment

Abstract: Background Schizophrenia involves alterations in hippocampal function. The implications of these alterations for memory function in the illness remain poorly understood. Furthermore, it remains unknown how memory is impacted by drug treatments for schizophrenia. The goal of this study was to delineate specific memory processes that are disrupted in schizophrenia and explore how they are affected by medication. We specifically focus on memory generalization - the ability to flexibly generalize memories in novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 38 publications
7
29
0
Order By: Relevance
“…By contrast, prior studies with the computer-based acquired equivalence task have reported much better performance particularly in control groups, with control groups often averaging at or below 10–15% errors on generalization pairs (20, 21, 34), although one prior study using an Australian sample found error rates of about 31% in healthy elderly subjects (41). These prior studies did not include separate reward- and punishment-based trials; rather, on each trial the subject received explicit reward (feedback and point gain) for a correct response or explicit punishment (feedback and point loss) for an incorrect response.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…By contrast, prior studies with the computer-based acquired equivalence task have reported much better performance particularly in control groups, with control groups often averaging at or below 10–15% errors on generalization pairs (20, 21, 34), although one prior study using an Australian sample found error rates of about 31% in healthy elderly subjects (41). These prior studies did not include separate reward- and punishment-based trials; rather, on each trial the subject received explicit reward (feedback and point gain) for a correct response or explicit punishment (feedback and point loss) for an incorrect response.…”
Section: Discussionmentioning
confidence: 74%
“…Patients symptomatic for early (AD) show similar deficits on generalization, although they also show slower learning than age-matched controls, consistent with a more diffuse pattern of accumulating brain pathology in early AD (19). Disrupted generalization on acquired equivalence tasks is also seen in other psychopathologies that commonly involve hippocampal-region volume reductions, including schizophrenia (20, 21) and post-traumatic stress disorder (22). …”
Section: Introductionmentioning
confidence: 99%
“…According to recent findings in humans, memory generalization does not rely solely on inferential processes that take place during retrieval, but also relies on integrative and constructive processes already at the time of encoding (Shohamy and Wagner, 2008). Such processes have been associated with functional coupling of the hippocampus and midbrain: phasic dopaminergic firing in response to novel stimuli is thought to trigger reactivations of related or overlapping representations of prior memories and thus result in updating through integration of new information into existing memory (Kumaran and Duzel, 2008;Shohamy and Wagner, 2008;Shohamy et al, 2010). It is therefore possible that the overgeneralization of memory representations that results in a positive response bias is caused by stress-induced tonic activation of this circuit.…”
Section: Discussionmentioning
confidence: 99%
“…In schizophrenia, dysregulation of dopamine in the hippocampus does seem linked to mnemonic dysfunction, suggesting that restoring “normal” levels is advantageous (Shohamy et al, 2010). These results suggest similar dynamics for dopamine in the medial temporal lobes and the basal ganglia, yet many questions remain regarding the mechanisms of dopamine action in the medial temporal lobes; findings of distinct dopamine receptor distribution in the basal ganglia vs. the medial temporal lobes suggest possibly distinct modes of action in these regions (see Shohamy & Adcock, 2010 for detail).…”
Section: Interactions Between the Basal Ganglia And Other Brain Symentioning
confidence: 99%